2001
DOI: 10.1037/0893-3200.15.4.688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interpersonal control, perspective taking, and attributions on older mothers' and adult daughters' satisfaction with their helping relationships.

Abstract: Older mother-adult daughter dyads (N = 44) were interviewed separately about 3 variables hypothesized to affect satisfaction with the help provided to mothers by their daughters: feelings of interpersonal control, perspective-taking abilities, and attributions made about the self and other dyad member during positive and negative helping interactions. The most important predictors of partner satisfaction were mothers' and daughters' ability to accurately perceive the partner's feelings about the helping relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…Both Cook (1993) and Lachman and Weaver (1998) found that individuals felt more control within family ties characterized by high relationship quality. Similarly, Martini et al, (2001) found that mothers' and daughters' relationship satisfaction and perceptions of control were positively associated. Conversely, Cook (1993) found high negative reciprocity was associated with lower perceived control in nuclear family ties.…”
Section: Characteristics Of Relationships and Perceptions Of Control mentioning
confidence: 91%
See 1 more Smart Citation
“…Both Cook (1993) and Lachman and Weaver (1998) found that individuals felt more control within family ties characterized by high relationship quality. Similarly, Martini et al, (2001) found that mothers' and daughters' relationship satisfaction and perceptions of control were positively associated. Conversely, Cook (1993) found high negative reciprocity was associated with lower perceived control in nuclear family ties.…”
Section: Characteristics Of Relationships and Perceptions Of Control mentioning
confidence: 91%
“…Rather, such perceptions reflect the features of each relationship. A number of studies employing different methodologies and focusing on various relationships indicate that individuals typically feel more control over high-quality relationships, and less control over problem-ridden relationships (Cook, 1993;Lachman & Weaver, 1998;Martini, Grusec, & Bernardini, 2001). Both Cook (1993) and Lachman and Weaver (1998) found that individuals felt more control within family ties characterized by high relationship quality.…”
Section: Characteristics Of Relationships and Perceptions Of Control mentioning
confidence: 99%
“…The older generation typically values the intergenerational relationship more than the younger generation (Bengtson & Kuypers, 1971; Fingerman, 2001; Martini, Grusec, & Bernardini, 2001). Similarly, mothers-in-law may be more knowledgeable of their future child-in-law, rate the relationship more positively, and have more positive expectations of the tie.…”
Section: Other Variables Associated With Relationship Patternsmentioning
confidence: 99%
“…The present research did not specifically address interpersonal control or ways of initiating help or types of help given as proposed by (Martini, Grusec, & Bernardini, 2001. However, the conclusions of these researchers are similar to those of the present study; there is a need to elucidate some of the factors that contribute to positive helping exchanges in elderly mother-adult daughter dyads.…”
Section: Discussionmentioning
confidence: 57%